Pengembangan Ensiklopedia Materi Vertebrata Kelas X SMA/MA sebagai Media Pembelajaran - Prycila Anggi Prasetia Hutagalung; Rahmadina Rahmadina (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to develop a valid encyclopedia of vertebrate biodiversity and to receive positive responses from students and teachers at SMA Swasta Gajah Mada Medan. The research method used is Research and Development (R&D) with the Borg & Gall development model, which consists of 10 stages. The results show that media experts rated this product at 90%, categorized as "Highly valid." Material experts provided a rating of 93.75%, also categorized as "Highly valid." A limited product trial involving 20 students from class X MIA resulted in an N-Gain score of 0.65, classified as moderate. In a large-scale field trial, an N-Gain score of 0.61 was obtained, also classified as moderate. In conclusion, the vertebrate material encyclopedia is valid and suitable for use by students as a learning resource, as it has received positive evaluations. Keywords: Biology, Encyclopedia, Media, Development, Vertebrates.